2017
DOI: 10.1002/pon.4551
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing time to seeking medical advice and onset of treatment in women who are diagnosed with breast cancer in Serbia

Abstract: Several factors, related to psychological, demographic, behavioral, and health system characteristics, determined both the time to seeking medical advice and treatment onset for breast cancer. These findings support review and refining of national strategies and policies to promote early detection, diagnosis, and treatment of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
2
2
0
4
Order By: Relevance
“…Similarly, compared with studies in sub-Saharan African countries, the median patient interval in our study (30 days) was considerably shorter than those reported from Rwanda (150 days)24 and Mali (144 days),34 but comparable with that reported from South Africa (23 days) 35. As expected, compared with findings from countries outside of sub-Saharan Africa, however, our finding of median patient interval is generally longer 36 37…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, compared with studies in sub-Saharan African countries, the median patient interval in our study (30 days) was considerably shorter than those reported from Rwanda (150 days)24 and Mali (144 days),34 but comparable with that reported from South Africa (23 days) 35. As expected, compared with findings from countries outside of sub-Saharan Africa, however, our finding of median patient interval is generally longer 36 37…”
Section: Discussionsupporting
confidence: 79%
“…To reduce this interval, it would be important to remember that women with lower educational levels were more susceptible to have longer intervals, which is consistent with results from other studies 21,25,26 . Lower educational levels are also associated with lower levels of awareness and recognition of breast cancer warning signs 27,28 .…”
Section: Discussionsupporting
confidence: 83%
“…A semistructured interview guide was used for the interview. The guiding questions were based on previous similar publications 6,10,[15][16][17][18][19][20] and were adapted for use in the Ghana context. Section 1 of the interview guide (Supplementary Data) was semistructured, and it was based on the Model of Pathways to Treatment framework.…”
Section: Data Collectionmentioning
confidence: 99%